Study on fatigue life and fracture behaviour of fibreglass reinforced composites - Zakaria, Kamarul Ariffin; Jimit, Roy Hanson; Ramli , S.N.R.; Abdul Aziz, Azizuddin; Bapokutty, Omar; Ali, Mohd Basri (Universiti Malaysia Pahang, Malaysia, 2016)
The material used in vehicle parts could significantly affect the vehicle efficiency. Fibreglass reinforced composites are among the materials that can be used to manufacture the components due to their excellent lightweight properties. Composite structures may undergo fatigue failure when subjected to a certain number of cyclic loading, which normally occurs below the ultimate strength of the material. However, studies on this material’s behaviour remain lacking, including on its integrity under fatigue loading. This paper aims to emphasize a study on the effect of fibre orientation on fatigue strength of fibreglass reinforced composites (FGRC), which are [±45°] and [0/90°]. The composite is fabricated from unidirectional glass fibre and epoxy resin using a hand lay-up technique. The experimental test is carried out at room temperature according to ASTM D3039 for tensile test at rate 5mm/min and ASTM D3479 for fatigue test at R=0.1 subjected to constant amplitude loadings. The results were presented in the form of S-N curves, showing that [0/90°] orientation has a higher fatigue strength as a function of fibreorientation. The results show that the mechanical properties and fatigue behaviour were significantly affected by the fibre orientation of the FGRC